2017
DOI: 10.1038/ejcn.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and susceptibility to type 2 diabetes: an evolutionary perspective

Abstract: 1Type 2 diabetes is rapidly increasing in prevalence worldwide, in concert with epidemics of 2 obesity and sedentary behaviour that are themselves tracking economic development. 3Within this broad pattern, susceptibility to diabetes varies substantially in association with 4 ethnicity and nutritional exposures through the life-course. An evolutionary perspective may 5 help understand why humans are so prone to this condition in modern environments, and 6 why this risk is unequally distributed. A simple concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 96 publications
1
23
0
Order By: Relevance
“…Humans have a high proportion of body fat compared to other primates, and to mammals more widely (Pontzer et al, ; Wells, ; Zihlman & Bolter, ). In contrast, skeletal muscle mass (a major constituent of lean mass) is low compared with our closest relatives Pan (Zihlman & Bolter, ), other primates (Muchlinski, Snodgrass, & Terranova, ) and, it has been argued, earlier fossil hominin species (Churchill, ; Churchill, ; Trinkaus, ; Trinkaus et al, ; Wells, ). Within our species, fat and lean masses vary in relation to selective pressures such as climate and disease load (Houghton, ; Wells, ; Wells & Cortina‐Borja, ; Wilberfoss, ), and population variation in body composition is linked to contemporary disease susceptibility (Gysel et al, ; Lear, Kohli, Bondy, Tchernof, & Sniderman, ; Unni et al, ; Wells, ).…”
Section: Introductionmentioning
confidence: 89%
“…Humans have a high proportion of body fat compared to other primates, and to mammals more widely (Pontzer et al, ; Wells, ; Zihlman & Bolter, ). In contrast, skeletal muscle mass (a major constituent of lean mass) is low compared with our closest relatives Pan (Zihlman & Bolter, ), other primates (Muchlinski, Snodgrass, & Terranova, ) and, it has been argued, earlier fossil hominin species (Churchill, ; Churchill, ; Trinkaus, ; Trinkaus et al, ; Wells, ). Within our species, fat and lean masses vary in relation to selective pressures such as climate and disease load (Houghton, ; Wells, ; Wells & Cortina‐Borja, ; Wilberfoss, ), and population variation in body composition is linked to contemporary disease susceptibility (Gysel et al, ; Lear, Kohli, Bondy, Tchernof, & Sniderman, ; Unni et al, ; Wells, ).…”
Section: Introductionmentioning
confidence: 89%
“…However, the relationship between T2D and obesity may not necessarily be as direct as it appears. For instance, in countries such as China, India, and Japan, in which the prevalence of T2D is high, the prevalence of obesity is relatively low 12,14 . In contrast, in countries such as Australia and the United Kingdom, where the obesity prevalence is high, T2D prevalence is relatively low 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most individuals with T2D are overweight or obese, 11 and T2D patients who are not considered overweight or obese may still have a high percentage of body fat primarily in the abdominal region. [11][12][13] Current studies have indicated that impaired glycemic control and disease duration are the two major contributing factors that affect body composition in individuals with T2D. 14,15 However, data about fat distribution and variations in individuals with T2D are limited and equivocal.…”
Section: Introductionmentioning
confidence: 99%